Influence of land use on the trophic niche overlap of dung beetles in the semideciduous Atlantic forest of Argentina. Issue 6 (9th May 2018) - Giménez Gómez, Victoria C.; Verdú, José R.; Gómez‐Cifuentes, Andrés; Vaz‐de‐Mello, Fernando Z.; Zurita, Gustavo A.
Abstract: The degradation and replacement of natural ecosystems affect species abundance, diversity and interspecific interaction through the modification of resource availability and environmental conditions. Land uses preserving the forest canopy show higher species richness and similarity to the native forest. In this study, we explored changes in the trophic niche overlap of dung beetles between the native forest and different land uses in the semideciduous Atlantic forest, under the hypothesis that trophic niche overlap increases with species richness. We sampled dung beetles in protected native forests and four land uses (pine plantations, agroforestry parklands, silvo‐pastoral systems and open pastures), using seven potential food sources (monkey, feline, tapir and deer dung, decomposing fruit, decomposing fungi and carrion). The species richness of each habitat, the trophic niche overlap and the relation between both measures were analysed. Also, we explored species trophic preferences in each habitat to explain and discuss the results obtained in trophic niche overlap measures. As expected, our results showed a positive relation between species richness and trophic niche overlap. Moreover, the addition of different resources in open habitats did not increase species richness, suggesting that resource availability may not be the main mechanism explaining the empoverished dung beetle community observed in open habitats. Other mechanisms, such as physiological restrictions, may play a role in limiting the use of these habitats. Studies on the mechanisms leading to the patterns of species abundance and diversity observed in land uses are necessary to propose management recommendations that increase the sustainability of open habitats.